Online Workflow Puzzle - Hoffman-Walbeck, Thomas; Adams, Richard (Journal of Graphic Engineering and Design, 2021)
We are presenting an online workflow puzzle, which runs in a browser. The player can put together puzzle pieces to pre-defined production chains. Extensive online help supports the player in laying out the puzzle pieces correctly. The puzzle is based on the process-resource model, which is also the basis of the Job Definition Format. This paper explains the game as well as implementation strategy. Article history: Received (June 1, 2020); Revised (September 4, 2020); Accepted (September 7, 2020); Published online (March 1, 2021)